Considerations on the dimensioning of columns with dimensions less than that established by NBR 6118 (ABNT, 2014) (Research, Society and Development, 2021)
The search for methods that provide savings greatly drives the search for alternatives when it comes to cost reduction. The obsession with aesthetics and cheaper alternatives for civil construction, can lead to unexpected and dangerous results. The reduction of the dimensions of the columns can be done consciously, always keeping in mind the compliance with normative standards combined with structural optimization. The objective of this work was to evaluate the efforts resulting from the reduction of the minimum dimensions beyond that established by NBR 6118 (ABNT, 2014) and compare with the considerations of NBR 15575 (ABNT, 2013) about a possible permission to reduce the minimum dimensions of columns. For this, the software MathCAD, Eberick and SAP2000 were used to implement the calculation and design methods of the columns. The variables evaluated were the steel area of ​​columns with different cross sections, length of buckling and the necessary anchoring length that a beam would need to anchor in the columns. As a result, it was found that in relation to the steel area, the decrease in the section resulted in increases in the steel area. The buckling was not acceptable (λ> 140) with a cross-section column less than 19 cm for situations of double height up to 6 m in height, according to NBR 15575 cites. The criterion of anchoring the beam reinforcement in a column with section smaller than 14 cm was not feasible for all situations.